Alterations in composition of immune cells and impairment of anti-tumor immune response in aged oral cancer-bearing mice. (December 2019) - Sekido, Katsuhisa; Tomihara, Kei; Tachinami, Hidetake; Heshiki, Wataru; Sakurai, Kotaro; Moniruzzaman, Rohan; Imaue, Shuichi; Fujiwara, Kumiko; Noguchi, Makoto
Highlights: Immune regulatory cells significantly increase in oral cancer, with advancing age. PD-1 and CTLA-4 expression is elevated in T cells of aged oral cancer-bearing mice. Proliferation of T cells from aged oral cancer-bearing mice is decreased. Immunotherapies targeting PD-1, CTLA-4, and PD-L1 are more effective in aged mice. Abstract: Objectives: Aging has been suggested to be associated with immune dysregulation. An understanding of alterations in the host immunity with advancing age is, therefore, important for designing immune therapy for elderly cancer patients. In this context, not much is known about age-associated alterations in the immune system in oral cancer. Methods: To evaluate age-associated alterations in the immune system, which might affect anti-tumor immune responses in oral cancer, we performed a comparative analysis of the proportion of different immune cells, the proliferative capacity of T cell compartment, and the response against immune therapies targeting immune check point molecules between young and aged oral cancer-bearing mice. Results: The proportion of immune regulatory cells, such as regulatory T cells and myeloid derived suppressor cells, was significantly increased in aged mice compared to that in young mice. Moreover, the expression of PD-1 and CTLA-4 on both CD4 + and CD8 + T cells was elevated in aged mice compared to that in young mice, and the proliferative abilities of CD4 + and CD8 + T cells derived from aged mice were significantly reduced following stimulation of T-cell receptors. Moreover, tumor growth was significantly enhanced in aged mice compared to that in young mice. However, immunotherapies targeting PD-1, CTLA-4, and PD-L1 resulted in faster tumor regression in aged mice than in young mice. Conclusions: Together, our results indicate that age-associated alterations in the immune system are directly associated with the impairment of anti-tumor immunity in aged mice bearing oral cancer, and might facilitate the progression of the tumor.